Wind energy status in electrical energy production of Turkey - Güler, Önder (Elsevier BV, 2009)
Abstract Main electrical energy sources of Turkey are thermal (lignite, natural gas, coal, fuel oil, etc.) and hydraulic. Most of the thermal sources are derived from natural gas. Turkey imports natural gas; therefore, decreasing usage of natural gas is very important for both economical and environmental aspects. Because of disadvantages of fossil fuels, renewable energy sources are getting importance for sustainable energy development and environmental protection. Among the renewable sources, Turkey has very high wind energy potential. However the installed wind power capacity is only 0.22% of total economical wind potential. In this study, Turkey's installed electric power capacity, electric energy production is investigated and also Turkey current wind energy status is examined.